2014
DOI: 10.1016/j.mad.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and extravascular distribution of the ATP-binding cassette transporters ABCB1 and ABCC1 in aged human brain and pituitary

Abstract: ATP-binding cassette (ABC) transporters play an increasing role in the understanding of pathologic peptide deposition in neurodegenerative diseases (NDs), such as Alzheimer’s and Parkinson’s. To describe the location of the most important ABC transporters for NDs in human brain tissue, we investigated ABCB1 and ABCC1 immunohistologically in the adult human brain and pituitary. Both transporters have similar but not identical expression patterns. In brain regions with an established blood-brain barrier (BBB), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Yet another—less explored—possibility is that the ABCB1 and CYP2D6 polymorphisms are also related to pharmacodynamic effects. According to a recent publication, in addition to BBB, P‐gp is expressed in parenchymal central nervous system cells including neurons (Bernstein et al, ). There is also published information available indicating that, in the plasma membrane, P‐gp interacts physically and functionally with caveolin‐1 (Cav‐1), another membrane protein that is important for synaptic signalling, dendritic arborization, and neuronal survival (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet another—less explored—possibility is that the ABCB1 and CYP2D6 polymorphisms are also related to pharmacodynamic effects. According to a recent publication, in addition to BBB, P‐gp is expressed in parenchymal central nervous system cells including neurons (Bernstein et al, ). There is also published information available indicating that, in the plasma membrane, P‐gp interacts physically and functionally with caveolin‐1 (Cav‐1), another membrane protein that is important for synaptic signalling, dendritic arborization, and neuronal survival (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Due the contribution of ABC transporters on Aβ clearance in AD, they have been proposed as potential therapeutic targets (Krohn et al, 2011). Moreover, ABCB1 dysfunction has been also associated with other neurodegenerative disorders such as PD, progressive supranuclear palsy (PSP) or genetically associated with depressive disorders (Bernstein et al, 2014). As most of these efflux pumps are up-regulated by Nrf2, using Nrf2 activators may provide an important tool to increase the activity of ABC transporters.…”
Section: Abc Transportersmentioning
confidence: 99%
“…Furthermore, several anticancer drugs such as camptothecins, epipodophyllotoxins, and certain tyrosine kinase inhibitors (TKIs) are recognized by all three ABC transporters (sharing substrate range). Hence, the sole inhibition or downregulation of one transporter can be compensated by the upregulation of another . Moreover, it was recently shown that these transporters might be simultaneously expressed, which extends the cross‐resistance of cancer cells regarding used antineoplastic agents (differing substrate range).…”
Section: Introductionmentioning
confidence: 99%
“…and HL60/R-CP164 ),6-mercaptopurine (T-ALL165 ) methotrexate (CEM/MTX166,167 ), mitoxantrone (DON/MX0.004-0.016168 ), or6-thioguanin (T-ALL 165 )Anti-inflammatory and antipyretic agents. The nonsteroidal anti-inflammatory drug sulindac, a reverser of MRP1mediated MDR,169 had also the ability to increase MRP1 gene expression (amongst other transporters) in HT29 human colon carcinoma cells 170.…”
mentioning
confidence: 99%